The Interplay between Daptomycin and the Immune System - Kelesidis, Theodoros (Frontiers in Immunology, 2014)
Antibiotics may have bacteriostatic or bactericidal effects but may also cause immunomodulation. Lipopeptides are known immunomodulators that interact with pattern recognition receptors (PRRs) such as Toll-like receptors (TLRs) in antigen presenting cells. Daptomycin is a novel lipopeptide antibiotic with a lipid moiety and unique structure that in the presence of divalent ions may directly interact with lipid membrane phospholipids, the major component of lipid membranes in immune cells. Daptomycin may also penetrate immune cells including neutrophils and macrophages. However, the possible immunomodulatory effects of daptomycin remain unknown. Understanding these effects is important to determine whether this agent can provide protection against infectious challenge through multiple mechanisms. Preliminary studies suggest that daptomycin may have minimal effects on cytokine production and may have synergistic immunomodulatory effects in combination with other immunomodulators. This review focuses on the hypothesis that daptomycin may also have immunomodulatory effects but further studies are needed to investigate this hypothesis.